Abrus Agglutinin, a type II ribosome inactivating protein inhibits Akt/PH domain to induce endoplasmic reticulum stress mediated autophagy‐dependent cell death. Issue 2 (31st May 2016) - Panda, Prashanta Kumar; Behera, Birendra; Meher, Biswa Ranjan; Das, Durgesh Nandini; Mukhopadhyay, Subhadip; Sinha, Niharika; Naik, Prajna Paramita; Roy, Bibhas; Das, Joyjyoti; Paul, Subhankar; Maiti, Tapas K.; Agarwal, Rajesh; et al.
Abstract : Abrus agglutinin (AGG), a type II ribosome‐inactivating protein has been found to induce mitochondrial apoptosis. In the present study, we documented that AGG‐mediated Akt dephosphorylation led to ER stress resulting the induction of autophagy‐dependent cell death through the canonical pathway in cervical cancer cells. Inhibition of autophagic death with 3‐methyladenine (3‐MA) and siRNA of Beclin‐1 and ATG5 increased AGG‐induced apoptosis. Further, inhibiting apoptosis by Z‐DEVD‐FMK and N‐acetyl cysteine (NAC) increased autophagic cell death after AGG treatment, suggesting that AGG simultaneously induced autophagic and apoptotic death in HeLa cells. Additionally, it observed that AGG‐induced autophagic cell death in Bax knock down (Bax‐KD) and 5‐FU resistant HeLa cells, confirming as an alternate cell killing pathway to apoptosis. At the molecular level, AGG‐induced ER stress in PERK dependent pathway and inhibition of ER stress by salubrinal, eIF2α phosphatase inhibitor as well as siPERK reduced autophagic death in the presence of AGG. Further, our in silico and colocalization study showed that AGG interacted with pleckstrin homology (PH) domain of Akt to suppress its phosphorylation and consequent downstream mTOR dephosphorylation in HeLa cells. We showed that Akt overexpression could not augment GRP78 expression and reduced autophagic cell death by AGG as compared to pcDNA control, indicating Akt modulation was the upstream signal during AGG's ER stress mediated autophagic cell death. In conclusion, we established that AGG stimulated cell death by autophagy might be used as an alternative tumor suppressor mechanism in human cervical cancer. © 2016 Wiley Periodicals, Inc.